The Revival of Aesthetics: In a Few Words - Erjavec, Aleš (Filozofski vestnik, 2007)
The immediate reason for choosing the theme of this international issue of Filozofski vestnik was the forthcoming XVII International Congress of Aesthetics (Ankara, July 2007). The other motive was to discern some of the issues in contemporary aesthetics.